Pengaruh Pemberian Terapi Oksigen Hiperbarik Terhadap Kadar Kolesterol Total Pada Tikus Putih (Rattus novergicus) Jantan Galur Wistar Yang Diinduksi Diet Tinggi Lemak - AZRUL HILDAN SAFRIZAL (HANG TUAH MEDICAL JOURNAL, 2018)
ABSTRACT BACKGROUND: The pattern and lifestyle of today's society with the presence of an interner facility makes people spend more time sitting out than on exercise and increased consumption of high-fat foods may increase the risk of cardiovascular disease. An effective therapy is needed in preventing the occurrence of cardiovascular disease. Hyperbaric oxygen now starts to develop for the treatment of several diseases, which in turn can increase the gene forming antioxidant enzymes and ROS.To determine effect of hyperbaric oxygen therapy on total cholesterol levels of wistar white rats (Rattusnovergicus) induced by high fat. METHOD: The study was carried out in an experimental post test only group of three groups. First group was given standard feed. Second group was given high-fat diet. Third group was given high fat diet and hyperbaric oxygen therapy with a dose 2 ATA 3 x 30 minutes for six days. On day 7 total cholesterol levels were measured. RESULT: One way Anova test showed that high fat diet incresed total cholesterol level (p = 0.03) and oxygen hyperbaric therapy significantly decreased total cholesterol level (p=0,015). CONCLUSION : hyperbaric oxygen therapy significantly decreased total cholesterol level because can increase the gene forming antioxidant enzymes and ROS